Spectra of the photo-electric phenomena physically differentiated on the light absorption factor - Berezhinsky, L.I.; Venger, E.F.; Matyash, I.E.; Serdega, B.K. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2004)
The pleochroism phenomena in photoconductivity of Ge samples and gate photoelectomotive force (photo-emf) of Si samples were experimentally investigated by a polarization modulation method. Anisotropy of dielectric properties was created by uniaxial compression. The spectral characteristics of the polarization difference describing above effects were measured. We found that: а) the pleochroism spectrum of
photoconductivity is a derivative with respect to the absorption factor of a photocurrent function; b) the pleochroism spectrum of the gate photo-emf contains dichroic components, determined by the sample thickness, diffusion length of majority carriers, and layer thickness of a spatial charge.